An insight into rheumatology in Thailand - Louthrenoo W. (Nature Publishing Group, 2015)
© 2015 Macmillan Publishers Limited. All rights reserved. Despite the fact that rheumatic diseases constitute a common health care problem in Thailand, improvements in rheumatology education, research and health care are still required. Low numbers of rheumatologists, their uneven distribution, lack of time to perform both clinical and basic research, lack of patient compliance and restricted access to effective medication comprise some of the barriers that need to be overcome to establish rheumatology education, research and care with a Western-country benchmark. The annual academic activities provided by the Thai Rheumatism Association for rheumatologists, general practitioners, allied health professionals and patients can advance only some forms of education and health care. Better cooperation between the Thai Rheumatism Association, the Royal College of Physicians of Thailand, the Ministry of Public Health and the Thai government is needed to improve rheumatology training, care and research in the country.